2023
DOI: 10.3390/ani13101650
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania Animal Models Used in Drug Discovery: A Systematic Review

Abstract: Many different animal models are in use for drug development for leishmaniasis, but a universal model does not exist. There is a plethora of models, and this review assesses their design, quality, and limitations, including the attention paid to animal welfare in the study design and execution. A systematic review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines of available literature after the year 2000 describing animal models for leishmanias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Another study showed that researchers are concerned with ethical issues and discuss these with their peers [12]. Nevertheless, there still seems to be less focus on the 3Rs when sharing information on, e.g., animal models used in drug discovery [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that researchers are concerned with ethical issues and discuss these with their peers [12]. Nevertheless, there still seems to be less focus on the 3Rs when sharing information on, e.g., animal models used in drug discovery [13].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, it is not disclosed to which extent preclinical animal experimental publications mention and promote 3R approaches. However, systematic reviews of preclinical animal experimental studies within specific science fields have shown that there is a gap when evaluating 3Rs practices [13,15]. Nevertheless, such a straightforward information route would provide researchers with 3Rs information relevant to their own field of science.…”
Section: Introductionmentioning
confidence: 99%